Analysis of T-cell repertoire diversity in Wiskott-Aldrich syndrome - Wada, Taizo (© 2005 by The American Society of Hematology, 2005)
Wiskott-Aldrich syndrome (WAS) is an X-linked immunodeficiency characterized by thrombocytopenia, eczema, and variable degrees of impaired cellular and humoral immunity. Age-dependent T-cell lymphopenia has been described in WAS, however, the diversity of the T-cell compartment over time in these patients has not been characterized. We have used complementarity-determining region 3 (CDR3) size distribution analysis to assess T-cell receptor (TCR) Vβ repertoire in 13 patients with WAS. Diverse CDR3 size pattern was demonstrated in patients under 15 years of age regardless of the levels of WAS protein (WASP) expression. In contrast, older patients showed significantly higher skewing of TCRVβ repertoire as compared with healthy adults. We did not find correlation between clinical score and complexity of TCRVβ repertoire. These findings suggest that WASP deficiency does not limit thymic generation of a normal TCR and indicate that T-cell oligoclonality may contribute to the immunodeficiency in older patients with WAS.